Kualitas air disekitar lokasi budi daya ikan di Desa Paslaten Kabupaten Minahasa - Yahuli, Yason; Pangemanan, Pankie N.L; Rompas, Robert J (e-Journal BUDIDAYA PERAIRAN, 2014)
The purpose of this study was to determine the current state of water quality in fish farming locations in the waters of Lake Tondano . Sampling points at each station are placed vertically in three predetermined points from the guard house to the front of the net.  The distance between one sampling  point to the next was ± 10 m. Water quality including physicals and chemicals parameters were analyzed at the Industrial Research Board of Manado. Sampling  point was made purposively as refers to the physiographic location in order to represent or describe these waters condition. This study was conducted for 2 weeks. Water sampling was done in three times, in the  morning, at noon, and in the evening. Direct measurement (in situ) was performed once a week that included DO, pH, temperature, and brightness, while the laboratory tests were conducted for 2 weeks which included phosphate, turbidity, Nitrite, Nitrate. Research results  showed that temperature, DO, pH, brightnes, phosphate, turbidity, nitrite, nitrate are still in good condition based on water quality standard stated in PP No.82 of 2001 . Keywords: Lake Tondano, water quality, chemical Parameter, physical Parameter